If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=1/3(3)-3
We simplify the equation to the form, which is simple to understand
y=1/3(3)-3
Simplifying:
y=0.333333333333*(3)-3
Reorder the terms in parentheses
y=+(+1)-3
Remove unnecessary parentheses
+y=+1-3
We move all terms containing y to the left and all other terms to the right.
+1y=+1-3
We simplify left and right side of the equation.
+1y=-2
We divide both sides of the equation by 1 to get y.
y=-2
| 8(4-4)=-5k-32 | | a^2-ax+4bx-16b^2= | | X=.8x+2.8 | | -2(u+3)=3u+4 | | -32=4(x-5)-6x | | 8N+(N-5)4-9N=2N-15 | | 450x=10560 | | 3+n/3=6 | | -8+5(3a-2)=4(2a+1)+6 | | cosx+3sinx=2 | | x/3+3=4 | | 37f-24f=-26 | | -6y-12+2y=28 | | 1/4x+1/2x=-1/8 | | y=-14/3(12) | | 4n+8=-24 | | -4/5-1/3w=-1/2 | | y=28/3/-1/2 | | 2(8+f)=22 | | 7(7x-77)=98 | | 100(b-3)=450-50b | | X=.8x+4 | | -7x-4(x+10)=-139 | | 2.33333333333= | | -3g-g=24 | | 7(h-1)=3(h+1/3) | | r/6=14 | | 5x+3y=x | | 24a-12a=24 | | 2r+200=2000 | | y=-25/5(12) | | 16x^2+40x+15=0 |